I Claudius: A nostalgically-charged evaluation of Claude Megson’s heyday in the 1970s - Wood, Peter (Architectural History Aotearoa, 2022)
Along with Ian Athfield and Roger Walker, Claude Megson emerged in the early 1970s as an idiosyncratic architectural iconoclast utterly committed to the New Zealand house. However, Megson’s legacy has taken a different course to his compatriots. Unlike Athfield and Walker, Megson had no literary champion to promote his significance (it might be said he had his own voice for that). Moreover, his relatively early death in 1994 curtailed his architectural activity but there was little indication in his work by then that he would either continue to reinvent his approach to housing in the manner of Walker, or grow his scope and scale of his work like Athfield. By the mid 1970s Megson had formed a rigid approach to domestic work that underpinned – and probably limited – his activities as an architect and architectural educator. His certainty on this matter also polarised opinion on his personality. You were obliged to be either with or against Claude, and this dialectical distinction has not endeared him to researchers. In this paper I wish then to evaluate the historical significance of Megson in three interlocking parts. The first concerns his personal mythology as an architect hero in the manner of Frank Lloyd Wright (a narrative that real estate agents are quick to promote his work). The second part is found in an analysis of his actual houses from this period with particular attention given to his masters’ dissertation. The final aspect I wish to weave through is his presence as a dominant personality, but a rather marginal teacher, at the Auckland School of Architecture into the 1980s. This will not be a particularly scholarly or academic appraisal. In keeping with the complexities and paradoxes that underpinned Megson’s character, what I hope to do here is to provide a sketch for further scholarship on one of New Zealand’s most intriguing architects.